Psychology's Stewardship of Gender/Sex. (November 2021) - Schudson, Zach C.
Psychological theories of gender and/or sex (gender/sex) have the capacity to shape people's self-perceptions, social judgments, and behaviors. The institutional power of psychology to affect cognition and behavior—not just to measure them—necessitates a serious consideration of our social responsibility to manage the products of our intellectual labor. Therefore, I propose that psychological research should be understood as stewardship of gender/sex (and socially relevant concepts in general). In this issue, four articles collectively serve as a demonstrative slice of the diversity of current directions in psychological research on gender/sex. I use these articles as springboards for articulating key elements of psychologists' stewardship of gender/sex and strategies for improving our stewardship. First, I examine how psychology's historical stewardship of gender/sex has yielded both new methods for self-understanding and harmful consequences for marginalized people. Next, I explore promising current approaches that center minoritized perspectives. I also discuss roadblocks to effective stewardship, including narrowly disciplinary approaches. Finally, I consider strategies for improving psychology's stewardship of gender/sex, such as mitigating gender/sex essentialism and employing generative theoretical frameworks built from interdisciplinary insights.